IMPLEMENTATION HUMAN RESOURCE MANAGEMENT IN IMPROVING COMPETITIVE ADVANTAGE of PT CSI - Rina Trinovianti; Sangkala Ruslan (Dinasti Publisher, 2021)
This researchXaims to analyzeXthe implementation of the integration process of the company's strategic plan and HRD strategic plan in increasing competitive advantage in PT CSI. The research dataXis collectedXfrom in-depth interviews and secondary data as well as primary data from HRD in 2019. Qualitative research methods with approaches case studies are used in this study. The results of the study found that the implementation of Human Resource Management has not been oriented towards comprehensive investment. It is proven that HRD is still considered a cost center, even though there has been an integration and adaptation of the entire process of increasing competitive advantage. HRD companies have been involved in the planning process. The day-to-day practice of Human Resource Management does not appear to fully describe the integration with the needs of organizational strategy. The results also show that at the practical level HRD has a two-way relationship with policy makers, meaning that the problems and impacts that arise in HR management are considered in the strategic plan formulation process.